รูปแบบการนิเทศที่ส่งผลต่อการปฏิบัติหน้าที่สอนของครูประถมศึกษาที่สอนไม่ตรงวิชาเอกของครูโรงเรียนประถมศึกษาขนาดเล็กสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - เพ็ญรุ่ง คำจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study aimed to explore the instructional supervision models that impact the teaching performance of primary school teachers who teach subjects outside their fields at small-sized primary schools under the Office of Basic Education Commission. The population was teachers of small-sized primary schools under the Office of Basic Education Commission. The sample was 278 teachers of small-sized schools under the Primary Educational Service Area Office 2 of Roi Et province affiliated with the Office of Basic Education Commission. A 5 - point Likert scale questionnaire was used as the research instrument. The data were analyzed using the calculations of frequencies, percentages, means and standard deviations as well as multiple regression analysis. The examined supervisory types were Clinical Supervision, Cooperative Professional Development, Self-Directed Development and Administrative Monitoring. The findings indicated that 1) Self-sufficient instructional supervision had the most impact on teaching performance with a positive correlation and the variance was 8.5% statistically significant at 0.001 level. 2) Self-sufficient instructional supervision had the most effect on performance of teaching learning management through thinking, real practice, and daily life application with a positive correlation and the variance was 8.2% statistically significant at 0.001 level. 3) Self-sufficient instructional supervision affected the most on performance of teaching use of media, technology, and learning resources which are conducive to learning. It was positively correlated and the variance was 4% statistically significant at 0.001 level. 4) Self-sufficient instructional supervision impacted the most on performance of teaching positive classroom management with a positive correlation and the variance was 10% statistically significant at 0.001 level. 5) Self-sufficient instructional supervision had the most impact on performance of teaching systematic examination, assessment and development of learners. It had a positive correlation and the variance was 6.3% statistically significant at 0.001 level. 6) Self-sufficient instructional supervision had the most effect on performance of teaching knowledge exchange and feedback providing to improve and develop learning management. It was positively correlated and the variance was 4.3% statistically significant at 0.001 level.